2013
DOI: 10.1155/2013/175012
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Keratinolytic Protease from New Wool-DegradingBacillusSpecies Isolated from Egyptian Ecosystem

Abstract: Novel keratin-degrading bacteria were isolated from sand soil samples collected from Minia Governorate, Egypt. In this study, the isolates were identified as Bacillus amyloliquefaciens MA20 and Bacillus subtilis MA21 based on morphological and biochemical characteristics as well as 16S rRNA gene sequencing. B. amyloliquefaciens MA20 and B. subtilis MA21 produced alkaline keratinolytic serine protease when cultivated in mineral medium containing 1% of wool straight off sheep as sole carbon and nitrogen source. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 43 publications
7
23
2
Order By: Relevance
“…Similar reports were made in case of B. amyloliquefaciens MA20 and for B. cereus [22,23]. The Bacillus subtilis VCDA isolated from C. diffusa showed an optimum 48 U/ml activity at temperature 40°C Anand et al, isolated Halobacterium sp.…”
Section: Discussionsupporting
confidence: 65%
“…Similar reports were made in case of B. amyloliquefaciens MA20 and for B. cereus [22,23]. The Bacillus subtilis VCDA isolated from C. diffusa showed an optimum 48 U/ml activity at temperature 40°C Anand et al, isolated Halobacterium sp.…”
Section: Discussionsupporting
confidence: 65%
“…Keratinases are usually active in alkaline conditions and reported pH optima ranges from pH 8.0 to 10.0 [36,74,95,132] with exception of acidic pH optima which is usually found in case of keratinases from fungal sources and extremely basic pH optima also exists. [52,133] Nam et al, [48] reported that keratinase from Fervidobacterium islandicum AW-1 with a temperature optima of 100 C, is one of the most thermostable keratinases reported to date. Temperature optima of keratinases range from 40 to 80 C, as reported by various workers.…”
Section: Keratinases: Biochemical Propertiesmentioning
confidence: 99%
“…Thereafter, it decreased slowly to the minimum at 9.0. Another study reported similar optimum pH for protease production (36). Furthermore, there were also reports that the best pH for protease production was 8.0(37), 9.0 (38), 10.0 (39), and 11.0 (38,40).…”
Section: Optimization Of Culture Conditions For Proteasementioning
confidence: 71%